2021
DOI: 10.1038/s41368-021-00124-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde nerve growth factor signaling modulates tooth mechanical hyperalgesia induced by orthodontic tooth movement via acid-sensing ion channel 3

Abstract: Orthodontic tooth movement elicits alveolar bone remodeling and orofacial pain that is manifested by tooth mechanical hyperalgesia. Nerve growth factor (NGF) is upregulated in periodontium and may modulate tooth mechanical hyperalgesia. The objectives were to examine the role of NGF in tooth mechanical hyperalgesia and to elucidate the underlying mechanisms. Tooth mechanical hyperalgesia was induced by ligating closed coil springs between incisors and molars in Sprague–Dawley rats. Retrograde labeling was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Similar perineuronal plexuses around large diameter neurons have also been seen in the affected sensory ganglia after various types of peripheral nerve injury in mice (Lee et al, 1998;Minett et al, 2014;Ramer et al, 1997 and rats (Chung et al, 1993(Chung et al, , 1996(Chung et al, , 1997Jones et al, 1999;Li et al, 2011;McLachlan et al, 1993;Ramer et al, 1999;Zhou et al, 1996). Notably, sympathosensory sprouting has been reported in the human DRG (García-Poblete et al, 2003;Shinder et al, 1999). Though the neurochemical phenotype of those sensory neurons targeted after peripheral nerve injury remains elusive, NGF likely contributes to sympathosensory sprouting seen in NGF transgenic mice, as well as in adult rodents and humans with nerve injury.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Similar perineuronal plexuses around large diameter neurons have also been seen in the affected sensory ganglia after various types of peripheral nerve injury in mice (Lee et al, 1998;Minett et al, 2014;Ramer et al, 1997 and rats (Chung et al, 1993(Chung et al, , 1996(Chung et al, , 1997Jones et al, 1999;Li et al, 2011;McLachlan et al, 1993;Ramer et al, 1999;Zhou et al, 1996). Notably, sympathosensory sprouting has been reported in the human DRG (García-Poblete et al, 2003;Shinder et al, 1999). Though the neurochemical phenotype of those sensory neurons targeted after peripheral nerve injury remains elusive, NGF likely contributes to sympathosensory sprouting seen in NGF transgenic mice, as well as in adult rodents and humans with nerve injury.…”
Section: Introductionmentioning
confidence: 56%
“…Another ion channel that is widely expressed in the TG is ASIC3, a proton‐gated acid‐sensing ion channel activated by acidosis resulting from tissue injury (Gao et al., 2021; Morgan et al., 2020; Stephan et al., 2018). ASIC3 is potentially involved in nociception and mechanosensation and displays extensive co‐expression with CGRP in TG and DRG neurons (Ichikawa & Sugimoto, 2004; Papalampropoulou‐Tsiridou et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Orofacial pain was induced by ligating closed coil springs between incisors and molars in rats to mimic orofacial pain induced by orthodontic tooth movement, and this orofacial pain rat model has been well documented by previous studies [ 2 , 6 , 11 ]. Specifically, following general anesthesia with pentobarbital sodium (50 mg/kg), rats were placed in supine positions, and the closed coil springs were stretched and activated to deliver force (40 g).…”
Section: Methodsmentioning
confidence: 99%
“…As an important protein in the process of neurogenesis and neuron growth, nerve growth factor (NGF) plays an important role in orofacial pain modulation [ 9 , 10 ]. Our previous study revealed that the administration of NGF into trigeminal ganglia could exacerbate orofacial pain [ 11 ]. Recent studies have also proved that NGF has been associated with the upregulation of CGRP, leading to neuroinflammatory pain response [ 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, ASIC3 was shown to contribute to orthodontic pain [ 239 , 240 , 241 ], and recent data show that periodontal acidification (around pH 7.0) induced by tooth movement results in mechanical tooth pain hypersensitivity that was partially reversed by an injection of APETx2 in the periodontal tissue in rats [ 242 ]. A genome-wide association study suggests that a genetic variation in the ASIC2 gene could be significantly associated with severe gingival inflammation, linked to periodontitis [ 243 ].…”
Section: Pathophysiological Relevance Of Asics and In Vivo Effects Of...mentioning
confidence: 99%